1934
DOI: 10.1021/ie50297a020
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Physiologically Neutral Fertilizer Mixtures - Reactions of Monoammonium Phosphate with Limestone and with Dolomite

Abstract: Monoammonium phosphate reacts with limestone in all proportions at ordinary temperatures in the presence of moisture to evolve carbon dioxide. Loss of ammonia takes place also when the CaC03 in the mixture exceeds one mole per mole of 03.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1936
1936
1949
1949

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The losses of carbon dioxide that take place with time from mixtures of 1 part diammonium phosphate and 1.14 parts limestone of varying particle size are shown by the curves in Figure 2. These curves indicate that the initial reaction is slower and more uniform than that in corresponding mixtures with monoammonium phosphate (2), and that the daily loss of carbon dioxide did not show any marked decrease until after 20 to 30 days. In the case of monoammonium phosphate-limestone (< 200-mesh) mixtures (2), nearly 80 per cent of the carbon dioxide was evolved in 10 days, and a marked decrease in the rate of the reaction was noted from that time until the completion of the reaction in about 60 days.…”
Section: Methodsmentioning
confidence: 75%
See 2 more Smart Citations
“…The losses of carbon dioxide that take place with time from mixtures of 1 part diammonium phosphate and 1.14 parts limestone of varying particle size are shown by the curves in Figure 2. These curves indicate that the initial reaction is slower and more uniform than that in corresponding mixtures with monoammonium phosphate (2), and that the daily loss of carbon dioxide did not show any marked decrease until after 20 to 30 days. In the case of monoammonium phosphate-limestone (< 200-mesh) mixtures (2), nearly 80 per cent of the carbon dioxide was evolved in 10 days, and a marked decrease in the rate of the reaction was noted from that time until the completion of the reaction in about 60 days.…”
Section: Methodsmentioning
confidence: 75%
“…The limestone and dolomite used in these tests were the same as those employed in the work reported previously (2). The compositions of the limestone and of the dolomite were as follows (in per cent): The different sized particles of limestone and dolomite used in the tests showed little variation in calcium carbonate equivalent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of ammonium compounds in the phosphatic mixtures does not interfere with the use of dolomite in such mixtures, for it was demonstrated by Maclntire and Sanders (4) that, at ordinary temperatures, ammoniates may be mixed with dolomite without loss of ammonia. A recent contribution by Beeson and Ross (1) showed that this also holds for monoammonium phosphate.…”
Section: Findings and Conclusionmentioning
confidence: 89%
“…The added limestone or dolomite kills off the "free" phosphoric acid, and thus mini- 1 In collaboration with the Division of Chemical Engineering, Tennessee…”
Section: Findings and Conclusionmentioning
confidence: 99%